2015
DOI: 10.1371/journal.pone.0133931
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin Family Members Drive Formation of Caveolae

Abstract: Caveolae are membrane organelles that play roles in glucose and lipid metabolism and in vascular function. Formation of caveolae requires caveolins and cavins. The make-up of caveolae and their density is considered to reflect cell-specific transcriptional control mechanisms for caveolins and cavins, but knowledge regarding regulation of caveolae genes is incomplete. Myocardin (MYOCD) and its relative MRTF-A (MKL1) are transcriptional coactivators that control genes which promote smooth muscle differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 64 publications
8
64
1
Order By: Relevance
“…Beyond the novel finding that cavin-2/SDPR is controlled by CEBPα/PPARγ in adipocytes, our results also confirm and extend the recent demonstration that myocardin family coactivators control the expression of caveolins and cavins [21]. In our previous study [21] we found that myocardin and MKL1 control gene expression of cavolins and cavins in smooth muscle.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Beyond the novel finding that cavin-2/SDPR is controlled by CEBPα/PPARγ in adipocytes, our results also confirm and extend the recent demonstration that myocardin family coactivators control the expression of caveolins and cavins [21]. In our previous study [21] we found that myocardin and MKL1 control gene expression of cavolins and cavins in smooth muscle.…”
Section: Discussionsupporting
confidence: 90%
“…This study, in conjunction with our previous work [21], thus highlights a considerable divergence between different cells types with regard to transcriptional control mechanisms of caveolar constituents. Such diversity may allow for tissue-specific pharmacological manipulation of caveolar function in diabetes and obesity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Expression data for the human coronary artery was downloaded from the GTExPortal.org and TMM normalized as described 34 . Panels A though C show relative expression levels for NOTCH ligands ( A ), receptors ( B ), and coactivators ( C ).…”
Section: Resultsmentioning
confidence: 99%
“…Myocardin family coactivators appear unique in that they induce essentially all caveolins and cavins [14]. Several questions remain unanswered with respect to this transcriptional control mechanism, however [4].…”
Section: Introductionmentioning
confidence: 99%